Genetic analysis of fruit sugar content in melon (Cucumis melo L.) based on a mixed model of major genes and polygenes - YE Hongxia; LÜ Lü; HAI Rui; HU Yuqing; WANG Bingliang (浙江大学学报. 农业与生命科学版, 2019)
Sugar contents of six generation populations (P1, P2, F1, F2, B1 and B2) derived from the cross between low sugar content inbred line ‘Huapicaigua’(Cucumis melo var. conmmon Makino) and high sugar content inbred line ‘XLH’(Cucumis melo var. saccharinus Naud.) were determined by high performance liquid chromatography (HPLC) method. Fruit sugar related traits in melon were analyzed using the joint segregation analysis method of a mixed major gene plus polygene genetic model. The results showed that the genetic model E-0, incorporating two pairs of additive-dominance-epitasis major genes plus an additive-dominance-epitasis polygene, was the best-fitting genetic model for fruit fructose content; and the genetic model E-1, incorporating two pairs of additive-dominance-epistasis major genes plus an additive-dominant polygene, was the optimal genetic model for fruit glucose, sucrose and total sugar contents. The fructose, glucose, sucrose, and total sugar contents were all controlled by two pairs of major genes and polygenes; the additive effect of major genes was mainly negative, and the interaction between the major genes was in common. Among them, the dominant and dominant interaction effect of the major genes for fructose, glucose and total sugar contents were the strongest, while the dominant and additive interaction effect of the major genes for sucrose content was the strongest. The negative additive effect of polygenes for sucrose and total sugar contents was relatively obvious. The heritabilities of major genes in the F2 populations conferring the fructose, glucose, sucrose and total sugar contents were 85.7%, 86.2%, 92.7% and 85.0%, respectively; and the environment showed very little effect for fruit sugar content. Thus, in melon breeding, selection for high sugar content in early generation melon is desirable.